Punk et violence en Normandie (1976-1980) - Christophe Pécout (Criminocorpus)
A land of rock’n’roll since the sixties, very close to London and with independent record shops, Normandy opened up to punk in 1976. A few groups formed and rushed into the punk adventure. The punk movement, which carries within it violence (musical, physical, aesthetic) offers its groups the opportunity to express their revolt and rage.